STATISTICAL ANALYSIS OF HOUSEHOLD MONEY - V. N. Salin; N. N. Kachanova; I. Y. Glebkova (Финансы: теория и практика)
The article investigates into household money, in particular, people’s savings that are used to acquire financial assets. The main economic problem in Russia is to attract and stimulate investments in the industrial sector. In conditions of sanctions imposed by Western governments on our country, internal sources of financing the economy are fundamental. This entails the issue of attracting free financial resources of households. The research topic is highly relevant. Creating a mechanism for accumulating and effective investing of household savings would also preserve and increase people’s savings under conditions of rising inflation. In this connection, the authors have considered the issues of formation of personal finance as it is a real basis for determining consumer demand. They show that households are important economic actors. The study demonstrates how households’ financial flows are interrelated with other sectors of the national economy as well as the possibility and the need to attract free financial resources of households (household savings) to increase the volume of domestic investment in the country’s economy. The authors have analyzed the amount, structure as well as dynamics in personal savings in the forms of deposits and securities.